Punitive Action Against Residents of Onuškis and Daugai Suspected of Collaboration With The Soviets in August 1945 - Tumavičius, Andrius (Genocidas ir rezistencija, 2025)
The present article focuses on a punitive operation in which partisans shot several dozen people suspected of collaborating with the Soviets. The objective of the present study is to ascertain whether this operation constituted an organised and targeted reprisal against collaborators with the intention of disrupting the process of Sovietisation, or whether it was an unwarranted terrorist attack motivated by revenge and desperation. The article examines the preparations for the punitive operation and identifies some of the participants. It also analyses the execution of the attack and identifies its victims. The study concludes that the operation was an attack in keeping with the conditions of the time: the partisans were retaliating in order to demonstrate their power to the regime. On the one hand, the operation was planned: the data on the condemned was collected, the action plan was in place, etc. On the other hand, it was a spontaneous decision by a few commanders, driven more by emotion than by well-thought-out tactical objectives. The partisans targeted the most vulnerable: the lowest administrative ranks, family members of the regime’s supporters or peasants. The attack did not target any official from the municipal administration or any individual involved in the deportations of July 1945.